PENYULUHAN HUKUM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) SEBAGAI UPAYA KEPASTIAN DAN PERLINDUNGAN HUKUM MASYARAKAT DESA PRASUNG SIDOARJO - yana indawati (Faculty of Law, 2020)
Legal certainty in land ownership is proof of physical and non-physical ownership of land rights. The ownership of the certificate does not merely fulfill administrative requirements, and only formal evidence. The certificate as a proof of rights that acts as a strong proof of physical data and juridical data contained in it, as long as the physical data and juridical data are in accordance with the data in the relevant land certificate and land book. In general, the amount of land owned by the people of Prasung Village, Buduran District, Sidoarjo Regency, both for agriculture and for settlements is still not certified. Legal counseling on land registration is very important because the natural potential and the development of such a large industry will be even more optimal if the community land is certified. This legal education is very necessary to be made so that people become aware of the importance of ownership of land certificates especially the use of land in the village of Prasung is partly used for tourist areas, plantation land, agriculture, settlements and public facilities. The response of the people of Prasung Village, Buduran Subdistrict was very positive and enthusiastic. The community hopes that things which become obstacles in registering land can be overcome.